2006
DOI: 10.1007/bf03021528
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal sufentanil is effective for postoperative analgesia in adults

Abstract: Purposes:The aim of this prospective, randomized, doubleblind study was to compare two doses of intranasal sufentanil for postoperative analgesia, titrated according to individual requirements based upon a numeric rating scale (NRS) from 0 to 10 for pain.Methods: Forty patients, American Society of Anesthesiologists physical status I-II, scheduled for herniorrhaphy or hemorrhoidectomy under general anesthesia, were included when postoperative NRS was > 3. Nurses used a nasal puff device delivering a constant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Absorption parameters for nasal sufentanil were similar to those reported by others in adults where T max occurred at 10 min . Absorption of intranasal ketamine was more rapid than that reported by others where T max was 18–20 min , which is considerably longer than T max of 8.5 (CV 17.3%) min in the present study. This may be due to administration of ketamine as nasal drops in previous studies, while intranasal sufentanil/ketamine in the present study was administered as a nasal spray that distributes to a greater surface area of the nasal cavity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Absorption parameters for nasal sufentanil were similar to those reported by others in adults where T max occurred at 10 min . Absorption of intranasal ketamine was more rapid than that reported by others where T max was 18–20 min , which is considerably longer than T max of 8.5 (CV 17.3%) min in the present study. This may be due to administration of ketamine as nasal drops in previous studies, while intranasal sufentanil/ketamine in the present study was administered as a nasal spray that distributes to a greater surface area of the nasal cavity.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, combinations of sufentanil approximately 1 mcg·kg or ketamine 5 mg·kg with midazolam 0.3 mg·kg have been used for preinduction of anesthesia/postoperative analgesia . However, sufentanil nasal spray 0.5 mcg·kg −1 has been investigated for analgesia in adult patients, achieving pain relief after surgery or from limb extremity injuries .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Mathieu et al in a recent study showed that efficacy was reached 20 minutes after internal administration of sufentanil. 3 They also reported that intranasal 0.050 g ϫ kg per puff of sufentanil resulted in a score less than 4 on a numeric rating scale (within 1 hour) in all patients who received the sufentanil.…”
Section: Dear Editormentioning
confidence: 98%